2015
DOI: 10.1007/s00284-015-0840-8
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Copper Alloys Against Invasive Multidrug-Resistant Nosocomial Pathogens

Abstract: The emergence and spread of antibiotic resistance demanded novel approaches for the prevention of nosocomial infections, and metallic copper surfaces have been suggested as an alternative for the control of multidrug-resistant (MDR) bacteria in surfaces in the hospital environment. This study aimed to evaluate the antimicrobial activity of copper material for invasive MDR nosocomial pathogens isolated over time, in comparison to stainless steel. Clinical isolates of methicillin-resistant Staphylococcus aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…2). A. baumannii clinical isolates have previously been shown to be sensitive to copper-containing metal coupons (50)(51)(52). The data cannot be compared directly due to protocol differences, but similar trends were observed, with full survival on control surfaces, significant reductions on coppercontaining surfaces, and more efficient killing by alloys with a higher copper content.…”
Section: Figmentioning
confidence: 89%
“…2). A. baumannii clinical isolates have previously been shown to be sensitive to copper-containing metal coupons (50)(51)(52). The data cannot be compared directly due to protocol differences, but similar trends were observed, with full survival on control surfaces, significant reductions on coppercontaining surfaces, and more efficient killing by alloys with a higher copper content.…”
Section: Figmentioning
confidence: 89%
“…While 63% of participants believed of nonessential, wash their hands. [26] In this case, the necessity for health personnel's implementation of education programs is inevitable. Investigation on hand washing understanding of importance among nurses showed that 40 min face-to-face education significantly effect on increasing the quality and quantity of hand washing.…”
Section: Hands Washing a Prerequisite For Infection Controlmentioning
confidence: 99%
“…On the other hand, copper containing brass showed no major differences in the total bacterial aerobic count loads for door handles and front door handles compared with reference surfaces (20 AE 70 CFU cm À2 and 9 AE 17, P > 0Á05, n = 37) in these real life circumstances. The antimicrobial efficiency of pure copper has been shown to be higher than that of copper alloys such as brass (Noyce et al 2006a;Koseoglu Eser et al 2015;San et al 2015). In the present study, brass and reference material door handles and front door handles had a low occurrence of Gram-negatives, S. aureus and enterococci, respectively (Table 2).…”
Section: Resultsmentioning
confidence: 48%
“…; Koseoglu Eser et al . ). Real life studies in hospitals have shown reduced total microbial counts and a lower occurrence of pathogens in the presence of copper surfaces, such as VRE or MRSA (Casey et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation